DHA e docosanoides promovem neurogênese e angiogênese com melhora da barreira hematoencefálica, área de infarto e escores neurológicos após isquemia-reperfusão cerebral focal em ratos - Freitas, Raul Sousa (2018)
DHA is a member of the essential omega-3 fatty acid family and is enriched in the membranes of the central nervous system. It is also necessary for the development of the nervous system, including vision. DHA has been shown to be involved in memory formation, synaptic membrane function, aging and neuroprotection. Studies have shown that DHA is a critical component of endogenous mechanisms that protect the brain after injury. DHA is the precursor of bioactive mediators, the docosanoids and neuroprotectin D1 (NPD1; 10R,17S-dihydroxy-docosa-4Z,7Z,11E,15E,19Z hexaenoic acid), is the first identified member of this group of mediators. Neuroprotectin D1 is produced at the onset of brain ischemia-reperfusion and its neuroprotective bioactivity includes inflammatory modulation, induction of cell survival, and restoring disrupted homeostasis. Although neurorestorative and neuroprotective actions of DHA have been demonstrated after experimental stroke, its mechanisms and the effect of NPD1 administration has not been fully characterized so far. To explore underlying mechanisms, SD rats underwent 2 h of middle cerebral artery occlusion (MCAo) and treated with DHA (5 mg/kg, IV) or NPD1 (5 μg/per rat, ICV) and vehicles 1 h after. Neuro-behavioral assessments were conducted on days 1, 2, and 3, and on week 1, 2, 3, or 4. BrdU was injected on days 4, 5, and 6, immunohistochemistry was performed on week 2 or 4, MRI on day 7, and lipidomic analysis at 4 and 5 h after onset of stroke. DHA improved short- and long-term behavioral functions and reduced cortical, subcortical, and total infarct volumes (by 42, 47, and 31%, respectively) after 2 weeks and reduced tissue loss by 50% after 4 weeks. DHA increased the number of BrdU+/Ki-67+, BrdU+/DCX+, and BrdU+/NeuN+ cells in the cortex, subventricular zone, and dentate gyrus and potentiated NPD1 synthesis in the penumbra at 5 h after MCAo. NPD1 improved behavior, reduced lesion volumes, protected ischemic penumbra, increased NeuN, GFAP, SMI-71-positive cells and vessels, axonal regeneration in the penumbra, and attenuated blood-brain barrier (BBB) after MCAo. We conclude that docosanoid administration increases neurogenesis and angiogenesis, activates NPD1 synthesis in the penumbra, and diminishes BBB permeability, which correlates to long-term neurobehavioral recovery after experimental ischemic stroke.